2021
DOI: 10.1155/2021/9986376
|View full text |Cite|
|
Sign up to set email alerts
|

FXYD6 Regulates Chemosensitivity by Mediating the Expression of Na+/K+-ATPase α1 and Affecting Cell Autophagy and Apoptosis in Colorectal Cancer

Abstract: Purpose. Chemoresistance is a challenge of improving chemotherapeutic efficacy and prolonging survival time for patients with colorectal cancer (CRC); it is the major cause of frequent recurrence, rapid metastasis, and poor prognosis for CRC patients. FXYD6 is a regulator of Na+/K+-ATPase which is depressed in chemoresistant CRC patients. However, the biological roles of FXYD6 on regulating chemoresistance in CRC are still unclear. Methods. GSE3964 and GSE69657 from GEO DataSets were used to analyze the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…To our knowledge, this is the rst study to demonstrate a link between ATP1A1 and resistance to targeted therapy. However, previous studies in other contexts have reported associations between ATP1A1 and chemoresistance [33,34], as well as ATP1A1 and senescence, which could potentially play a role in therapy resistance [35,36]. Since our data were obtained from a small cohort, it will be necessary to con rm these ndings with a larger population to establish whether ATP1A1 levels could be routinely evaluated to better de ne which melanoma patients would bene t from targeted therapy.…”
Section: Discussionmentioning
confidence: 84%
“…To our knowledge, this is the rst study to demonstrate a link between ATP1A1 and resistance to targeted therapy. However, previous studies in other contexts have reported associations between ATP1A1 and chemoresistance [33,34], as well as ATP1A1 and senescence, which could potentially play a role in therapy resistance [35,36]. Since our data were obtained from a small cohort, it will be necessary to con rm these ndings with a larger population to establish whether ATP1A1 levels could be routinely evaluated to better de ne which melanoma patients would bene t from targeted therapy.…”
Section: Discussionmentioning
confidence: 84%
“…We also noted dysregulation of cardiac hypertrophy through upregulation of F‐box protein 32 (FBXO32) and downregulation of prostaglandin E synthase (PTGES) (Al‐Yacoub et al, 2021; Degousee et al, 2008; Zeng et al, 2013). Downregulated genes also play a role in developmental processes and metabolism, (NKX6‐3) (Alanentalo et al, 2006), cell cycle regulation (TOB2) (Chen et al, 2020), and inhibition of apoptosis (FXYD6, NISCH) (Luo et al, 2021; Mukaddam‐Daher, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It functions as a receptor for both endogenous and exogenous ligands, activating different signaling pathways associated with cell survival, differentiation, proliferation, and apoptosis among other things. Although Luo and colleagues showed that the small membrane protein FXYD6 could increase NKA expression, whether it can improve sweat gland function remains to be determined ( 40 ).…”
Section: Discussionmentioning
confidence: 99%